The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5465/amr.2008.0038
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Stretch Goals: Organizations in Pursuit of the Seemingly Impossible

Abstract: We investigate the organizational pursuit of seemingly impossible goals-commonly known as stretch goals. Building from our analysis of the mechanisms through which stretch goals could influence organizational learning and performance, we offer a contingency framework evaluating which organizations are positioned to benefit from such extreme goals and which are most likely to pursue them. We conclude that stretch goals are, paradoxically, most seductive for organizations that can least afford the risks associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
184
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(191 citation statements)
references
References 94 publications
5
184
0
2
Order By: Relevance
“…By aspiring to improve their environmental performance in a significant manner, firms commit themselves to outcomes hitherto unthinkable and unobserved. Targets trigger cognitive and motivational processes (Sitkin et al 2011;Zhang and Jia 2013) which direct, energize, and encourage persistence needed to work toward their achievement, and which indirectly stimulate changed behaviors inside the organization (Locke and Latham 2009). Consequently, targets have the potential to unleash creativity, urgency, and excitement among employees with the purpose of collaborating, learning, innovating, and deviating from existing routines, habits, and practices to drive significant performance improvements (Halme 2002;Winter 2000).…”
Section: The Influence Of Climate Change Targets On Environmental Permentioning
confidence: 99%
See 1 more Smart Citation
“…By aspiring to improve their environmental performance in a significant manner, firms commit themselves to outcomes hitherto unthinkable and unobserved. Targets trigger cognitive and motivational processes (Sitkin et al 2011;Zhang and Jia 2013) which direct, energize, and encourage persistence needed to work toward their achievement, and which indirectly stimulate changed behaviors inside the organization (Locke and Latham 2009). Consequently, targets have the potential to unleash creativity, urgency, and excitement among employees with the purpose of collaborating, learning, innovating, and deviating from existing routines, habits, and practices to drive significant performance improvements (Halme 2002;Winter 2000).…”
Section: The Influence Of Climate Change Targets On Environmental Permentioning
confidence: 99%
“…Prior research has noted that the achievement of targets can be impeded when actors find it difficult to identify with them, or when targets provoke disappointment and demotivation because progress is slow. Particularly since climate change targets may by their nature be associated with significant uncertainty in relation to the processes and strategies for implementation, they can create internal resistance (Mishina et al 2010;Sitkin et al 2011;Zhang and Jia 2013). For example, there is the recognition that technological and operational "lock-in" due to long and large-scale investment cycles determines firms' performance levels for years if not decades (Unruh 2002).…”
Section: The Moderating Influence Of Firms' Carbon Dependencymentioning
confidence: 99%
“…For instance, some scholars have found that risk taking affects individual outcomes such as managers' subsequent changes in pay and long-term pay (Seo et al, 2014), satisfaction with firm performance , the CEO vega (i.e., CEO wealth associated with stock options) and the CEO's future risk taking (Coles et al, 2006). Other studies have shown how it affects firm outcomes (see Andersen et al, 2007;Bromiley et al, 2001;Nickel & Rodriguez, 2002;Ruefli, Collins & LaCugna, 1999)--principally firm performance (e.g., Bromiley, 1991;Strandholm et al, 2004;Villena et al, 2009) but also corporate restructuring and diversification (Hoskisson, Hitt, & Hill, 1991), firm recovery (Morrow et al, 2007), learning (Sitkin, See, Miller, Lawless, & Carton, 2011), survival/failure Latham & Braun, 2009), structure (environment-scanning, technocratization, differentiation : Miller et al, 1982), internationalization (Reuber & Fischer, 1997), product introduction divestiture (Hoskisson et al, 1994;Pathak et al, 2014), and BOD oversight of earning statements (Laux & Laux, 2009). …”
Section: Outcomes Of Managerial Risk Takingmentioning
confidence: 99%
“…As such, the idea of raising performance through clear goals (or stretch goals), creating commitment, and giving feedback are some of the strongest psychological guidelines in the business world (Hackman & Oldham, 1976;Locke, 1968Locke, , 2004Sherman, 1995;Sitkin, See, Miller, Lawless, & Carton, 2011), and exert mental pressure. However, this is not the same pressure as that felt when operating in the frontline of warfare.…”
Section: S Dynamics and Contextmentioning
confidence: 99%